2015
DOI: 10.1261/rna.052373.115
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for cooperative tandem binding of hnRNP C RRMs in mRNA processing

Abstract: The human hnRNP C is a ubiquitous cellular protein involved in mRNA maturation. Recently, we have shown that this protein specifically recognizes uridine (U) pentamers through its single RNA recognition motif (RRM). However, a large fraction of natural RNA targets of hnRNP C consists of much longer contiguous uridine stretches. To understand how these extended sites are recognized, we studied the binding of the RRM to U-tracts of 8-11 bases. In vivo investigation of internal translation activation of unr (upst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…Several experimental data proposed that multiple RRMs will help achieving higher affinity and specificity than the isolated RRM. 4,22 In this work, although the R38Q mutation does not directly act on the RNA-binding interface, some interfacial hydrogen bonds (Lys100-NZ:Cyt2-O2P and Met105-N:Cyt4-O2) are weakened because of the large fluctuations of RRM domains. Then, the calculated binding energy is increased in complex-R38Q system.…”
Section: Comparison Of Interactions In 3 Complex Systemsmentioning
confidence: 80%
“…Several experimental data proposed that multiple RRMs will help achieving higher affinity and specificity than the isolated RRM. 4,22 In this work, although the R38Q mutation does not directly act on the RNA-binding interface, some interfacial hydrogen bonds (Lys100-NZ:Cyt2-O2P and Met105-N:Cyt4-O2) are weakened because of the large fluctuations of RRM domains. Then, the calculated binding energy is increased in complex-R38Q system.…”
Section: Comparison Of Interactions In 3 Complex Systemsmentioning
confidence: 80%
“…Interestingly, Alu-exons with stable 3' splice site across primate species show an average U-tract length of 8–10 uridines (Figure 5A and B), which is at the lower limit of 9 to 10 uridines necessary to allow cooperative binding by the two RRMs of hnRNPC (Cieniková et al, 2015). We propose that a cryptic 3' splice site is best tolerated within an Alu element that already contains a long U-tract, while emergence of the same site in the absence of a long U-tract is subject to negative selection.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that the consensus RDE sequences are generally rich in multivalent binding sites for repressive RBPs. For instance, antisense Alus contain two separate U‐tracts that are often >8 nt long, and a U‐tract of 4 nts is sufficient to accommodate 1 RRM domain of hnRNPC . Thus, Alus with longer U‐tracts can accommodate multivalent binding of the four RRM domains of hnRNPC (two at each U‐tract), leading to high‐affinity binding.…”
Section: Exons Tend To Emerge From Rdes Through Gradual De‐repressionmentioning
confidence: 97%